How much does it cost to mitigate soil erosion after wildfires?. (15th May 2023) - Girona-García, Antonio; Cretella, Carola; Fernández, Cristina; Robichaud, Peter R.; Vieira, Diana C.S.; Keizer, Jan Jacob
Abstract: Wildfires usually increase the hydrological and erosive response of forest areas, carrying high environmental, human, cultural, and financial on- and off-site effects. Post-fire soil erosion control measures have been proven effective at mitigating such responses, especially at the slope scale, but there is a knowledge gap as to how cost-effective these treatments are. In this work, we review the effectiveness of post-fire soil erosion mitigation treatments at reducing erosion rates over the first post-fire year and provide their application costs. This allowed assessing the treatments' cost-effectiveness (CE), expressed as the cost of preventing 1 Mg of soil loss. This assessment involved a total of 63 field study cases, extracted from 26 publications from the USA, Spain, Portugal, and Canada, and focused on the role of treatment types and materials, and countries. Treatments providing a protective ground cover showed the best median CE (895 $ Mg −1 ), especially agricultural straw mulch (309 $ Mg −1 ), followed by wood-residue mulch (940 $ Mg −1 ) and hydromulch (2332 $ Mg −1 ). Barriers showed a relatively low CE (1386 $ Mg −1 ), due to their reduced effectiveness and elevated implementation costs. Seeding showed a good CE (260 $ Mg −1 ), but this reflected its low costs rather than its effectiveness to reduce soil erosion. The present results confirmed that post-fire soil erosion mitigation treatments are cost-effective as long as they are applied in areas where the post-fire erosion rates exceed the tolerable erosion rate thresholds (>1 Mg −1  ha −1 y −1 ) and are less costly than the loss of on- and off-site values that they are targeted to protect. For this reason, the proper assessment of post-fire soil erosion risk is vital to ensure that the available financial, human and material resources are applied appropriately. Highlights: The cost-effectiveness of post-fire soil erosion mitigation treatments was assessed. Agricultural straw and wood-residue mulches showed the best cost-effectiveness. Applying erosion mitigation measures is less costly than the loss of values-at-risk. Measures are most cost-effective when untreated erosion exceeds tolerable thresholds.